Peran self-efficacy dalam meningkatkan minat berwirausaha women entrepreneur yang dimediasi oleh pengetahuan kewirausahaan - Hartini Hartini; Aditya Wardhana; Normiyati Normiyati; Syarifuddin Sulaiman (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
This study was conducted to analyze the effect of entrepreneurial knowledge on self-efficacy; the effect of entrepreneurial knowledge on entrepreneurial intention; the effect of self-efficacy on entrepreneurial intention; the effect of entrepreneurial knowledge on entrepreneurial intention through self-efficacy. Using a quantitative research with an explanatory research survey method. Data analysis using path analysis through modeling of the Structural Equation Modeling (SEM) with AMOS. The data were collected through questionnaires to 120 women of fashion entrepreneurs in Makassar City, South Sulawesi. The results showed that entrepreneurial knowledge has a positive and significant effect on self-efficacy; entrepreneurial knowledge has a positive and significant effect on entrepreneurial intention; self-efficacy has a positive and significant effect on entrepreneurial intention; self-efficacy does not mediate the effect of entrepreneurial knowledge on entrepreneurial intention. The results of this study become a reference for women in conducting entrepreneurial activities and recognizing the influential aspects of entrepreneurship.